Bacteriorhodopsin expressed in Schizosaccharomyces pombe pumps protons through the plasma membrane. - Hildebrandt, V (1993)
Bacterioopsin (bO) from Halobacterium salinarium ("Halobacterium halobium") has been functionally expressed in a heterologous system, the fission yeast Schizosaccharomyces pombe. Regeneration of bO to bacteriorhodopsin (bR) in S. pombe has been achieved in vivo by addition of the chromophore retinal to the culture medium, as shown for a retinal-negative mutant of H. salinarium (JW5). Western blot analysis revealed that bR is more stable than bO against proteolysis in fission yeast and also in JW5. The light-driven proton pump is expressed in the eukaryotic organism and incorporated into the plasma membrane. Illumination of intact yeast cells leads to acidification of the external medium due to the translocation of H+ from inside to outside of the cell, indicating the same orientation of bR in the yeast plasma membrane as in H. salinarium. The kinetics of proton release into the water phase was observed with the optical pH indicator pyranine. Time-resolved absorbance changes of isolated plasma membrane measured by flash spectroscopy showed rise and decay of the M intermediate during the photocycle similar to those in the homologous system. Photocurrents and photovoltages were recorded with yeast plasma membrane attached to a planar lipid membrane and to a polytetrafluoroethylene (Teflon) film, respectively. Stationary currents measured in the presence of a protonophore showed continuous pumping activity of bR. The action spectrum of the photocurrent and the kinetics of the photovoltage were analyzed and compared with signals obtained from purple membranes. From all these different investigations we conclude that the integral membrane protein bR is correctly folded in vivo into the cytoplasmic membrane of the fission yeast S. pombe.